2003
DOI: 10.1200/jco.2003.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Sarcoma of Childhood and Adolescence: A Multicenter, Multivariate Analysis of Outcome

Abstract: Clinical group, tumor size, and invasiveness are important prognostic factors. Multicenter randomized clinical trials are needed to determine both the effect of chemotherapy on survival and the necessity of local radiotherapy in patients with completely resected tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
171
5
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 212 publications
(199 citation statements)
references
References 24 publications
11
171
5
4
Order By: Relevance
“…Radiotherapy is of most benefit with larger tumors and in the case of inadequate margins. This is consistent with other studies, 22 and in accordance with recent STS recommendations. 19,28 Original Article 2996…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Radiotherapy is of most benefit with larger tumors and in the case of inadequate margins. This is consistent with other studies, 22 and in accordance with recent STS recommendations. 19,28 Original Article 2996…”
Section: Discussionsupporting
confidence: 94%
“…A significantly better survival was previously demonstrated for patients aged <40 years, 10 17 years, 11 13 years, 22 and 35 years 23 ; the latter study included only patients with metastatic disease. Two other studies found age to be a continuous variable associated with survival.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the incidence rate of SS peaks in the third decade of life [1], 30% of SS cases occur in patients younger than 20 years of age [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most present with a painful lump which gradually grows over time. In pediatric cohorts, survival rates of up to 75-84% [2,[4][5][6][7][8][9] have been reported. These are superior to those reported in adults (survival rates ranging from 25-71%) [4,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%